SUDAH RAMAHKAH MASJID UNTUK KELOMPOK RENTAN? - Rahmad; Syar, Nur Inayah; Mualimin Sakarya Üniversitesi (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
The mosque as a place of worship for Muslims must be used by anyone. Mosques must also be open to anyone who wants to use the facilities for worship. However, the question is whether the mosque as a “God’s house” has been built by seeking facilities that can be used by vulnerable groups such as persons with disabilities or the elderly. This study aims to see how facilities at mosques that 'claim' to be vulnerable group-friendly mosques. This study will observe several existing facilities and be reviewed with certain criteria. The results of this study obtained data that the three Balum mosques could be said to be friendly to several facilities. However, we appreciate the efforts of mosque managers to create friendly facilities for vulnerable groups. The difficulty in fulfilling these facilities is the large investment that must be met by mosque managers in building accessible facilities